Las Competencias Específicas en la Conciliación Extrajudicial de Conflictos Socio-Ambientales del Abogado de la Universidad de la Costa-CUC (2018)
The present research work was developed, making an analysis of the academic curricula of the current Law programs in 3 universities of the city of Barranquilla, including the University of Costa CUC, from which arises the need to perform an analysis of the current situation of the country in relation to the way in which environmental conflicts are being resolved, the perception that exists in the imaginary of the population regarding them, the need to have professionals capable of resolving them and, consequently, the training that we give to the academy, taking into account the skills required for this purpose. The primary sources were the students of seventh and eighth semesters of the University of the Coast, community, legal professionals with training in conciliation, professors and professors of the law program and directors of conciliation and arbitration centers in the country and secondary sources they were regulations, laws, jurisprudence, among others. For the purposes of a specific analysis, the analysis of the legal competencies for Colombian lawyers, raised by Hernán Olano in 2007, was required; thus, as the competences of the conciliator lawyer suggested by (Gorjón, Steele, 2008) and, consequently, the specific competences for the conciliatory lawyer of socio-environmental conflicts graduated from the Universidad de la Costa, CUC are proposed.